URGENSI KONSELING KARIR DALAM PENGAMBILAN KEPUTUSAN KARIR (Hikmah, 2018)
Career is a part of life that affects the happiness of human life as a whore, career decision making is an action to be able to decide or make choise from various career options available. One of the theories of career decision making by Anna Roe says the developmental pattern of career selection will reflect the personal orientation that comes from the habit of parenting, he views career behavior is influenced by three components namely the imfluence needs. While theory of Tiederman that career choise there are two asfects of anticipation and accommodation. Career decision making in the counseling process is defining the times and formulating a number of alternatives, gathering information, processing information and making plants choosing goals and implementing plans with real forms.Keyword: Konseling karir, pengambilan keputusan karir.